Synthesis of Colloidal Mn2+:ZnO Quantum Dots and High-TC Ferromagnetic Nanocrystalline Thin Films - NORBERG, Nick S.; KITTILSTVED, Kevin R.; AMONETTE, James E.; KUKKADAPU, Ravi K.; SCHWARTZ, Dana A.; GAMELIN, Daniel R. (Journal of the American Chemical Society, 2004)
We report the synthesis of colloidal Mn(2+)-doped ZnO (Mn(2+):ZnO) quantum dots and the preparation of room-temperature ferromagnetic nanocrystalline thin films. Mn(2+):ZnO nanocrystals were prepared by a hydrolysis and condensation reaction in DMSO under atmospheric conditions. Synthesis was monitored by electronic absorption and electron paramagnetic resonance (EPR) spectroscopies. Zn(OAc)(2) was found to strongly inhibit oxidation of Mn(2+) by O(2), allowing the synthesis of Mn(2+):ZnO to be performed aerobically. Mn(2+) ions were removed from the surfaces of as-prepared nanocrystals using dodecylamine to yield high-quality internally doped Mn(2+):ZnO colloids of nearly spherical shape and uniform diameter (6.1 +/- 0.7 nm). Simulations of the highly resolved X- and Q-band nanocrystal EPR spectra, combined with quantitative analysis of magnetic susceptibilities, confirmed that the manganese is substitutionally incorporated into the ZnO nanocrystals as Mn(2+) with very homogeneous speciation, differing from bulk Mn(2+):ZnO only in the magnitude of D-strain. Robust ferromagnetism was observed in spin-coated thin films of the nanocrystals, with 300 K saturation moments as large as 1.35 micro(B)/Mn(2+) and T(C) > 350 K. A distinct ferromagnetic resonance signal was observed in the EPR spectra of the ferromagnetic films. The occurrence of ferromagnetism in Mn(2+):ZnO and its dependence on synthetic variables are discussed in the context of these and previous theoretical and experimental results.